Merjenje psihofizioloških odzivov pri bolnikih po preboleli možganski kapi med vadbo z robotsko napravo HapticMaster - Javh, Metka (Rehabilitacija (Ljubljana), 2011)
Background: The goal of our study was to evaluate psychophysiological responses of stroke patients during upper extremity exercise using the HapticMaster robot and a virtual environment. Methods: Four different psychophysiological responses (electrocardiogram, skin conductance, skin temperature and respiration rate) were measured in twenty-three stroke patients during rest and two different tasks performed with a haptic robot (cognitively undemanding uncoordinated movement and a cognitively demanding ball-catching game played in the virtual environment). Results: Psychophysiological measurements taken during rest were significantly different from measurements taken during tasks performed with the haptic robot. Skin conductance increased by (mean +- SD) 10.0 microS +- 21.8 during uncoordinated movement and by 20.0 mikroS +- 21.8 during the ballcatching game. Skin temperature increased by 0.2 K +- 0.6 (p < 0.01) during uncoordinated movement and decreased by 0.3 K +- 0.6 (p=0.24) during the ball-catching task. Changes in heart rate and respiration rate were small and not statistically significant. Conclusions: Skin conductance and skin temperature proved to be the most useful for psychological state estimation in stroke patients during robot-aided training in virtual reality. Changes in heart rate primarily reflected physical activity while changes in respiration rate were small and unreliable.
Keywords: haptični robot; možganska kap; navidezna resničnost; psihofiziologija; rehabilitacija; rehabilitacijska robotika; vocational rehabilitation